Optimizing Scientific Literacy: A Comprehensive Examination of the Effectiveness of Problem-Based Learning - Mulia, Mala; Susantini, Endang; Indana, Sifak (International Journal of Current Educational Research, 2024)
Objective: Able to face global challenges. One approach that has garnered attention is problem-based learning, considered capable of enhancing students' scientific literacy. This article aims to design and analyze the improvement of scientific literacy through problem-based learning methods. Method: The method employed in this research is a literature review. Results: The analysis revealed that PBL significantly improves students' scientific literacy skills. N-Gain values indicated moderate to high gains, and t-test results showed significance values below 0.05, confirming a substantial increase in scientific literacy after PBL implementation. Novelty: This article provides a comprehensive evaluation of Problem-Based Learning (PBL) in enhancing scientific literacy. Analyzing 15 selected studies, it shows significant improvements in students' scientific literacy skills, supported by N-Gain values and t-test results. The review highlights PBL's effectiveness, including the integration of technology, and offers robust evidence of its positive impact on students' ability to understand and apply scientific information, thus enriching the literature on effective teaching strategies.